Ultra-Reliable Low-Latency Communication in Beyond-4G Networks (International Journal of Engineering & Extended Technologies Research (IJEETR), 2021)
In light of the growing demand for real-time and mission-critical wireless applications, this paper explores Ultra-Reliable Low-Latency Communication (URLLC) within the paradigm of Beyond-4G networks, encompassing emerging 5G and preliminary beyond-5G (B5G) concepts as envisioned in 2020. We articulate the stringent requirements of latency (targeting sub-1 ms) and reliability (up to 99.999 %) necessary for applications such as autonomous vehicle control, remote surgery, and industrial automation. Key technical enablers—including short transmission time intervals, interface diversity, edge-centric architectures, and novel channel coding for finite blocklengths—are reviewed and synthesized. A conceptual framework combining redundant multi-interface transmission, edge-assisted scheduling, and lightweight reliability-enhancing physical layer mechanisms is proposed. The framework’s performance is evaluated through analytical modeling, focusing on latency distribution, packet delivery success, and spectral efficiency trade-offs. Results indicate that coordinated interface diversity with optimized payload distribution significantly enhances reliability and latency, compared to single-interface and naive redundancy approaches. Edge assistance further shifts processing closer to the user, reducing round-trip delays. However, gains come at the cost of increased complexity and potential fairness concerns among users. The findings highlight a balanced strategy impelling future URLLC design in Beyond-4G networks. Keywords, introduction, literature review, methodology, and subsequent sections flesh out the conceptual and analytical narrative, culminating in recommendations for future experimental and simulation validation.
Keywords: Ultra-Reliable Low-Latency Communication (URLLC); Beyond-4G networks (B5G); Edge computing / Mobile Edge Computing (MEC); Interface diversity; Finite blocklength coding; Mission-critical applications